2012
DOI: 10.1371/journal.pone.0049025
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Facilitation during Observation of Graspable Objects: A Transcranial Magnetic Stimulation Study

Abstract: In 1979, Gibson first advanced the idea that the sight of graspable objects automatically activates in the observer the repertoire of actions necessary to interact with them, even in the absence of any intention to act (“affordance effect”). The neurophysiological substrate of this effect was later identified in a class of bimodal neurons, the so-called "canonical" neurons, located within monkey premotor cortex. In humans, even if different behavioral studies supported the existence of affordance effect, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
7
44
2
Order By: Relevance
“…Indeed, these systematic activations occur extremely early. For instance, when participants are observing graspable objects, the increase in muscle excitability starts as early as 120 ms after the onset of the presentation (Franca et al, 2012). Similar delays were obtained in a study where participants learned to associate the contraction of the tibialis anterior muscle of each ankle in responses to an auditory cue (Schneider et al, 2004) or when measuring facial action (i.e., spontaneous mimicry) in response to the presentation of happy and neutral faces (Korb, Grangean and Sherer, 2010).…”
Section: Introductionsupporting
confidence: 62%
“…Indeed, these systematic activations occur extremely early. For instance, when participants are observing graspable objects, the increase in muscle excitability starts as early as 120 ms after the onset of the presentation (Franca et al, 2012). Similar delays were obtained in a study where participants learned to associate the contraction of the tibialis anterior muscle of each ankle in responses to an auditory cue (Schneider et al, 2004) or when measuring facial action (i.e., spontaneous mimicry) in response to the presentation of happy and neutral faces (Korb, Grangean and Sherer, 2010).…”
Section: Introductionsupporting
confidence: 62%
“…Accordingly, the inconsistent finding between the two studies is explained by a view that visual feedback eliminates the decrease in corticospinal excitability during eye movement in the hand muscles at rest. Indeed, simply observing an object increased corticospinal excitability in the hand muscles at rest (Franca, et al, 2012). In this study, automatic facilitation of the MEP in the opponens pollicis and the FDI muscles was observed within a small time interval after visual presentation of graspable objects.…”
Section: Eye Movement With Visual Occlusionsupporting
confidence: 49%
“…Not only motor commands to the eye muscles but also visual feedback occurs during eye movements. It has been reported that visual processing modulates corticospinal excitability; e.g., observing an object increased corticospinal excitability in the FDI and opponent pollicis muscles at rest (Franca, Turella, Canto, Brunelli, Allione, Andreasi, et al, 2012). Thus, the decrease in corticospinal excitability across the hand muscles during smooth pursuit eye movement observed in the previous study by Maioli, et al may be related to visual feedback rather than motor commands to the eye muscles.…”
Section: Introductionmentioning
confidence: 69%
“…Simply observing graspable objects within reaching distance can activate motor cortical networks suitable for grasping these objects, suggesting that we put our world into motor terms automatically [1][2][3][4][5][6]. This effect is evident as faster reaction times when hand responses are subliminally primed [7], but also using measures such as functional Magnetic Resonance Imaging [1] and Transcranial Magnetic Stimulation [6] to detect underlying changes in brain activity when viewing graspable objects. A direct link between visual perception and action offers a way to overcome transmission delays within a distributed nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…To address our specific aim, factors established in previous motor affordance research were used to inform a focused design. For example, past studies have shown that objects affording a particular type of grasp produce rapid excitability changes in muscles involved in grasping these viewed objects when they are within graspable range of the individual [2][3][4][5][6] but, this effect was absent when objects were out of reach, and for non-graspable 'control' objects [3]. Based upon this foundation we streamlined our approach to measure CSE in hand muscles during two distinct visual conditions: (i) viewing a wall-mounted safety handle or (ii) viewing no handle (i.e.…”
Section: Introductionmentioning
confidence: 99%